Pengaruh Model Problem Based Learning terhadap Hasil Belajar dan Keterampilan Proses Sains Siswa pada Materi Termokimia di Kelas XI SMA Negeri 1 Silaen - Chaterine Juliana Sitorus; Zuhairiah Nasution (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on student learning outcomes and science process skills in thermochemistry material. This study employed a quasi-experimental design with a pretest-posttest control group design. The research population was grade XI students of SMA Negeri 1 Silaen. Sampling was conducted using a random sampling technique, resulting in class XI-2 with 35 students as the experimental class implementing the Problem Based Learning model, and class XI-3 with 35 students as the control class using conventional learning. The results showed that the mean score of learning outcomes in the experimental class was 82.86 and the control class was 76.57. The hypothesis test showed > (3.859 > 1.667), indicating a significant effect of the problem based learning model on student learning outcomes in thermochemistry material. The average science process skills of the experimental class reached 82.46% categorized as very good, higher than the control class at 78.06% categorized as good. Correlation analysis using the product moment correlation obtained of 0.717, indicating a strong correlation between science process skills and learning outcomes, with a coefficient of determination of 51.44%. Thus, the problem based learning model is proven to effectively improve student learning outcomes and science process skills significantly in thermochemistry material.